The Influence of Family Relationship Patterns in Playing a Crucial Role in Forming Individual Identity and the Social Structure of Civil Society - Syam, Suriadi; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
In Islam, the family holds a central role in shaping both individual character and societal structure. From an individual perspective, the family nurtures core moral values such as strong faith in Allah, self-sacrifice, loyalty, and love for goodness. These values form the foundation for personal development and spiritual growth. Socially, the family is the primary institution for transmitting cultural values, traditions, and customs from one generation to the next, thereby ensuring societal continuity and cohesion. Beyond the transfer of material wealth, families pass on moral and ethical principles essential for life. The formation of a healthy, dynamic, and creative generation is a direct result of values instilled by the previous one. The kinship system, which encompasses relationships formed through blood, marriage, adoption, and social interactions, plays a pivotal role in defining social structure and obligations within society. Understanding these relationships is essential to comprehend how cultural and moral values are maintained and propagated. This paper provides a comprehensive overview of familial and kinship relationships and their broader implications in Islamic and anthropological contexts